Problems Of Teaching the Uzbek Language in Russian Groups - Aykhodjaeva Muborak Saidkarimovna (Euro Asian Journal Publishing, 2024)
The article talks about the problems of teaching the Uzbek language in Russian groups
Keywords: Grammar; predicative category; differentiated teaching; verb categories